Financial Performance and Capital Structure on Firm Value with Commodity Prices as a Moderating Variable - Sihombing, Pardomuan; Hutajalu, Clinton Banua Betlehem; Suparyati, Agustina (Research of Business and Management, 2023)
The objective of this study is to examine the impact of liquidity, profitability, and capital structure on firm value, with commodity prices as a moderating variable. Causal research was employed, and 23 companies were selected as samples using purposive sampling at the IDX. Secondary data from these companies were used for analysis, and panel data analysis with e-views was applied. The findings reveal that liquidity and profitability do not significantly influence firm value, while capital structure has a significant effect on firm value. Commodity prices moderate the relationship between profitability and firm value, but not for liquidity and capital structure. The study's implications suggest that coal mining companiesˑneed to carefullyˑconsider decisions that affect theirˑvalue, particularly regarding investment funding through the management of capital structure, profitability, and liquidity. For investors, it is crucial to make informed decisions based on firm value and performance, considering financial reports and stock price developments at IDX